1976
DOI: 10.1055/s-0028-1093645
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Altered Thyroid and Parathyroid Function on Reproduction in the Rat

Abstract: Mild maternal hypothyroidism produced by surgical thyroidectomy resulted in significantly reduced food intake along with retarded reproductive performance in rats. Hyperthyroidism increased food consumption above the control level along with an increase in fetal resorptions which was the only parameter of reproductive performance altered by the twenty-second day of gestation. In animals which underwent pregnancies, reproductive performance suffered a further decline in the second gestation due to increasing du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…We have found that if hypothyroidism (Tx) is induced on day 1 of gestation in the laboratory rat, reproduc tive performance of these animals is greatly impaired [19]. The fetuses of these Tx mothers are small for gestational age and the numbers surviving to term are greatly diminished.…”
mentioning
confidence: 99%
“…We have found that if hypothyroidism (Tx) is induced on day 1 of gestation in the laboratory rat, reproduc tive performance of these animals is greatly impaired [19]. The fetuses of these Tx mothers are small for gestational age and the numbers surviving to term are greatly diminished.…”
mentioning
confidence: 99%
“…Besides, it is well known that how nutritional restrictions and some hormones such as glucocorticoid [22], leptin [23,24], and insulin [25,26] affect the fetal programming; however, little is known about the role played by a low intake of thyroid hormones in critical stages of development and its impact on adult life. In this sense, several studies have reported that hypothyroidism seriously affects the reproductive performance of the female rats [27,28], which compromises the number of pups per litter. Also, the hypothyroid offspring often presents lower body mass at birth and a delay in the maturation of the central nervous system denoted by an increased eye-opening time [20,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the source for the increased glycogen synthesis in GH-treated Tx animals does not appear to be glucose per se (Porterfield and Hendrich 1976). These observations have provided further evidence that the fetal maldevelopment associated with maternal hypothyroidism (Porterfield, Whittle and Hendrich 1975;Porterfield and Hendrich 1975;Porterfield and Hendrich 1916;Hendrich, Porterfield, Henderson and Galton 1976) is not due entirely to self-imposed undernutrition (Hendrich et al 1976). Preliminary studies have shown also that the transfer of leucine-U-14 C from mother to fetus and its uptake by brain is impaired in Tx mothers (Hendrich and Porterfield (1980).…”
Section: Introductionmentioning
confidence: 84%